If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-112=4(-3+5z)
We move all terms to the left:
-112-(4(-3+5z))=0
We add all the numbers together, and all the variables
-(4(5z-3))-112=0
We calculate terms in parentheses: -(4(5z-3)), so:We get rid of parentheses
4(5z-3)
We multiply parentheses
20z-12
Back to the equation:
-(20z-12)
-20z+12-112=0
We add all the numbers together, and all the variables
-20z-100=0
We move all terms containing z to the left, all other terms to the right
-20z=100
z=100/-20
z=-5
| 2.5(6.25x+0.5)=11 | | 10-10p=-8-10+4p | | 59=9+5y | | (3)(x)=2x | | 34x–68=0 | | 11x=-9+2+x=-199 | | -5c-6=-8c+6 | | b8=5 | | 3×x+53=11 | | 5x-2(3x+6)=5x-2(3x+5) | | q+69=81 | | (-4)(x)=(1/2)x+1 | | 10x-5(x-2)=20 | | b+11=37 | | x-6=x/18 | | 3(x)=5x+1 | | f+31=57 | | y+6=88 | | 6d−14=34 | | 4p+5=377 | | 6.52+8.4t+9.5t=-3.84+3.1t | | -47=5x-3(x+19) | | 27=1-5x+6 | | 3(5−2n)+9n=-12 | | (3c-12)=-9 | | 1-5f=5-7f | | (x)=(1/2)x+1 | | 3(2x+4)+6(x+2)=48 | | 27=1-5x | | 8h+5=2 | | 75=5(t-70) | | 8u+10=9u-1+1 |